2020
DOI: 10.1111/are.14525
|View full text |Cite
|
Sign up to set email alerts
|

The effects of water additive Bacillus cereus and Pediococcus acidilactici on water quality, growth performances, economic benefits, immunohematology and bacterial flora of whiteleg shrimp (Penaeus vannamei Boone, 1931) reared in earthen ponds

Abstract: This study was aimed to investigate the effects of two probiotics, Bacillus cereus and Pediococcus acidilactici, on the water quality, growth performance, the survival ratio, economic benefits, immunohematology and bacterial flora in the intestine of whiteleg shrimp, Litopenaeus vannamei after 110 days. Nine earthen ponds (each one 1.2 hectare) were adjusted as three treatments including control (without adding bacteria), containing P. acidilactici probiotic (106 CFU/mL) and containing B. cereus probiotic (106… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 80 publications
(122 reference statements)
1
14
0
1
Order By: Relevance
“…Water supplements are used to adjust and stabilize the water quality parameters, microbiological and environmental conditions, as well as to suppress the growth of pathogenic microorganisms [30]. Water supplements are being used for purposes of bioremediation (known as water probiotics; [31,32]), alkalinity adjustment [33] and to regulate mineral levels [34][35][36].…”
Section: Super-intensive Production Systems and Strategiesmentioning
confidence: 99%
“…Water supplements are used to adjust and stabilize the water quality parameters, microbiological and environmental conditions, as well as to suppress the growth of pathogenic microorganisms [30]. Water supplements are being used for purposes of bioremediation (known as water probiotics; [31,32]), alkalinity adjustment [33] and to regulate mineral levels [34][35][36].…”
Section: Super-intensive Production Systems and Strategiesmentioning
confidence: 99%
“…B. cereus ATCC 14579 has the characteristic of synthesizing bacteriocin-like substances during growth and is able to inhibit the growth of pathogen-related bacteria such as Staphylococcus aureus and Micrococcus luteus [ 26 ]. A previous study reported that B. cereus could be a biological additive reagent to improve water quality, growth rate and immune response in cultivated shrimp [ 27 ]. Another candidate probiotic, P. fungorum , is a plant probiotic that can increase the growth and production of strawberries.…”
Section: Discussionmentioning
confidence: 99%
“…Improvement of pond microbiome also reduced NO 2 , total ammonia, sulphide metabolite, biochemical oxygen demand, and decomposition of organic materials (Khademzade et al . 2020). Differences in aquaculture practices also influence the microbiome composition.…”
Section: Influence Of Water Quality On Shrimp Microbiome and Healthmentioning
confidence: 99%